Kompetencja narracyjna jako obszar nauczania i oceny w edukacji - Soroko, Emilia; Wojciechowska, Julita (Wydawnictwo Naukowe UAM, 2015)
The article presents an analysis of the concept of narrative competence and its educational connotations. Narrative competence is increasingly recognized as the key area of an individual’s language skills. Definitions and differences between the aspects of narrative activity are described. Stages of development of narrative competence in relation to the general phenomena of development are selected and presented. The development of methods of stimulating the narrative competence in the educational process is indicated. Finally, analyzed are general issues related to the development of narrative skills at school: building “narrative” relationships and new ways of assessing learning outcomes.
Narrative Competence as an Area of Teaching and Assessment in Education
Keywords: education; narrative; narrative competence; narrative competence development